The Influence of Competence, Independence, and Audit Risks on the Auditor’s Ability to Detect Corruption with Integrity as a Moderating Variable - Husen Basri; Haryono Umar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to obtain empirical evidence of the effect of competence, independence, and audit risk on auditors’ ability to detect corruption with integrity as a moderating variable. The population in this study are auditors who work at financial auditor agencies. The sampling was performed using accidental sampling, while the primary data collection used a questionnaire method. The data were then analyzed using structural equation modeling (SEM) partial least square (PLS). The results showed that competence has a positive effect on the auditors' ability to detect corruption, while independence has no positive effect. Furthermore, audit risk has a positive effect on the auditors' ability to detect corruption, and integrity has a positive effect on their ability to detect corruption. Neither does integrity-moderated competencies strengthen the auditor’s ability to detect corruption nor integrity-moderated independence strengthen the auditor’s ability to detect corruption. Finally, integrity-moderated audit risk does not strengthen the auditor’s ability to detect corruption.